Peran Kelompok Wanita Tani Bersatu dalam Meningkatkan Pendapatan Keluarga di Desa Ginunggung Kecamatan Galang Kabupaten Tolitoli - Mahdar (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the role of the United Farmer Women's Group in increasing family income in Ginunggung Village, Galang District, Tolitoli Regency. This research was conducted at the United Farmer Women's Group in Ginunggung Village, Galang District, Tolitoli Regency on July 25, 2021 to August 25, 2021. This research uses a quantitative descriptive method. This data is processed using the income formula, household income, and income contribution. The results of this study indicate that the United Farmer Woman Group does not play a dominant role in increasing family income with only 9.53% income contribution which is categorized as non-dominant. Although not dominant, the income they earn is sufficient to supplement their household income. The role of the United Farmer Women Group in Ginunggung Village, Galang District, Tolitoli Regency is not only in the economic field but also in the social field, this is evidenced by the results of research that the United Women Farmers Group has social activities such as mutual cooperation and social gathering and they are trained to manage the group by good management.